Five Decades of Marine Megafauna Surveys from Micronesia - Martin, Summer L.; Van Houtan, Kyle S.; Jones, T. Todd; Aguon, Celestino F.; Gutierrez, Jay T.; Tibbatts, R. Brent; Wusstig, Shawn B.; Bass, Jamie D. (Frontiers in Marine Science, 2016)
Long-term data are critical for assessing the status, trends, abundance, and distributions of wildlife populations. However, such data streams are often lacking for protected species, especially highly mobile marine vertebrates. Using five decades of aerial surveys, we assessed changes in marine megafauna on the insular coral reef ecosystem of Guam (Marianas Archipelago in Micronesia). The data allowed estimates of relative abundance, trends, and geographic distributions for several important taxa: sea turtles, sharks, manta rays, small delphinids, and large delphinids. These surveys occurred in 32 years from 1963-2012 amounting to 632 flights lasting 809 hours over a 70.16 km2 area. Over this span, surveyors recorded 10,622 turtle, 1,026 shark, 60 manta ray, 7,515 small delphinid, and 95 large delphinid observations. Since the 1960s, sea turtles increased an order of magnitude (r = 0.07) and sharks decreased five-fold (r = -0.03). Turtle increases were largely restricted to one geographical area, where optimal habitat coincides with low human density and a marine protected area. Shark observations declined proximate to human population centers. Trends for the other taxa were less informative, but each taxon had geographic foci. Protections in the region may be working to recover turtle populations, but failing (or have not yet had sufficient time) to recover overfished shark populations. Long-term analyses of vulnerable marine megafauna in this data-limited region are uncommon, and should be used to guide more focused studies that inform regional management and conservation of these species.